Unveiling the Multifaceted Nature of Spirituality: Assessing the Dimensions of the Spirituality Inventory in the Turkish Context—A Preliminary Adaptation and Validity Reliability Study - Ekşi, Halil (Journal of religion and health, 2025)
The measurement of spirituality, a concept with significant implications for mental health, requires instruments that can assess its complexity and diversity without cultural limitations. This study adapts the Dimensions of Spirituality Inventory (DSI) into Turkish, examining its validity and reliability. A linguistic equivalence study with 43 participants showed coefficients between .79 and .91. The test-retest correlation coefficients of the subscales ranged from .35 to .78. The 53-item scale was then administered to 671 adults, and confirmatory factor analysis indicated an acceptable fit. The internal consistency reliability coefficient was .90. Positive correlations with related scales confirmed acceptable criterion-related validity. The study concluded that the Turkish version of the DSI is a valid and reliable tool for use in scientific research in Türkiye.